Redescription of Trichogrammatoidea annulata De Santis (Hymenoptera: Trichogrammatidae) - Querino, R. B.; Zucchi, R. A. (Zootaxa, 2004)
Trichogrammatoidea annulata is redescribed and most of the characters used for the redescription are illustrated. A key to the Brazilian species of Trichogrammatoidea is presented.